ANALISIS DAN KRITIK METODE HERMENEUTIKA AL-QUR’AN MUḤAMMAD SHAḤRŪR - Tarlam, Alam (IAIN Kediri, 2015)
Muá¸¥ammad Shaá¸¥rÅ«r is one of the leading contemporary Muslim scholars who criticized the methodologyÂ of Qurâ€™anic exegesis as developed by the classical Muslim exegetes. They said that those classical MuslimÂ interpreters treated the Qurâ€™anic textes in a passive and rigid manner, putting them out of the dialecticalcontext and contextualization. Consequently, understanding of the Qurâ€™an is ad hoc and partial. To overcomeÂ this problem, Shaá¸¥rÅ«r suggested a new method, approach, and procedure of reading the Qurâ€™an. This paperÂ will critically examine Shaá¸¥rÅ«râ€™s hermeneutical approach as a new method of reading the Qurâ€™an and otherreligious textes.Keywords: Muá¸¥ammad Shaá¸¥rÅ«r, Hermeneutika al-Qurâ€™an, Kontekstualisasi